An Analytical Study on Legal Validity of Online Dispute Resolution (ODR) System in India and Indonesia - Nikam, Dr Rahul; Nongthombam, Bangkim Singh (UI Scholars Hub, 2022)
Advancement in technology brought many inevitable changes with more efficiency, making human life easier. Benefit of technology shall be incorporated for effective and efficient justice delivery in dispute resolution mechanism. New development in this area is online arbitration dispute resolutions (ODR) which have been without doubt adopted and practices by justice delivery system across the globe. But the question remains the same as whether justice delivery system is equipped to cope up in the same pace with the changes taking place in the society and technology. Are the existing laws being enough to conduct online system as an effective mechanism to settle disputes among the parties? Keeping in context the preceding query, the present research resorted tracing the laws relevant to the use of ODR mechanism in India and Indonesia, as their present legal framework of arbitration addressing dispute resolution through the ODR mechanism lack specific laws. The present research adopts a mixed method using both primary and secondary data for tracing and comparison the ODR system in India and Indonesia. It is concluded that ODR deliverance are valid and enforceable in the present legal framework of both the countries. Therefore, people must not be doubtful while using ODR mechanism to settle their disputes. It also demonstrates that an ample scope is there in the existing laws of both the countries to accommodate and enhance the overall process and deliverance of ODR mechanism through amendments and separate guidelines.